طرق وإج ا رءات خوصصة البنوك والآثار الناجمة عنها - د ا رسة تجربة فرنسا، مصر والج ا زئر- - boufi, garmiya (Finance and Business Economies Review, 2018)
the public sector transformed into private sector or what is called “privatization”, It is one of the most remarkable global changes of the advanced and developing world economies during the two last decades of the twentieth century. The privatization realized a great success in advanced countries while developing and Arabic countries kept slowly advancing in crucial decisions taking concerning banks privatization. Indeed, the privatization process in these countries requires the obligation to qualify and adapt banks by restructuring which is considered as an essential basis for developing banks and adapting them to perform the privatization process